If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(m + -2) = 119 Reorder the terms: -7(-2 + m) = 119 (-2 * -7 + m * -7) = 119 (14 + -7m) = 119 Solving 14 + -7m = 119 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -7m = 119 + -14 Combine like terms: 14 + -14 = 0 0 + -7m = 119 + -14 -7m = 119 + -14 Combine like terms: 119 + -14 = 105 -7m = 105 Divide each side by '-7'. m = -15 Simplifying m = -15
| 6X+14=-10 | | (3x+5)+(3x-5)= | | 3x+4+5x+7= | | (3x+5)-(3x-5)= | | (v-7u-4)(5v+2)= | | 4y=-8x-32 | | 2x+2y=114 | | y^2-ay+8ab=0 | | x(81x-64)=0 | | x^4-13x^2-30=0 | | (x-4)(x^2+8x+7)=0 | | 7p^2=-12-44p | | 0.9(x+70)+0.7x=127 | | (4x^2-5x^3)-(2x^2-7x^3)= | | ax+7x+ay+7y=0 | | 6x^2-45-24=0 | | 272*67/68*3/16 | | 4(t-3)+4t=4(2t+5)-8 | | 2(t-3)+8t=5(2t+5)-11 | | 3x-1x=20 | | 2-(+0,8)/(0,5)= | | 3x+11=3x-11 | | 5+8p-2=4p+27-2p | | Ln(2x+1)=-4 | | B^2=3b+4 | | a/3-2 | | (4x+20)/(x-3)/(x+5)/(2x-6) | | x^2+4x=145 | | 16x^2+4x=4x+4 | | x^2+2x=113 | | 3xy+1=2y-5xfory | | 0-0+8=35 |